THE 4P’S MARKETING MIX VARIABLES: AN ASSESSMENT OF CONCEPT, APPLICABILITY AND IMPACT ON ORGANIZATIONAL GOAL FROM WEST JAVA’S BUSINESS ORGANIZATIONS - Harman Malau (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2020)
Effective marketing strategy enables marketers to create a combination of variables in managing wisely the company’s activities to achieve the expected goals. Now days, there are several approach methods that common practiced in marketing stategy which is called 4Ps. This research used independent variables that are place, price, promotion and place. And it’s dependent variable was organizational goal. This study were to investigate (a) the practice application of 4Ps on business organization and (b) to examine the impact of the 4Ps marketing variables on business performance in Indonesia (c) to examine the impact of the 4Ps marketing variables on business performance in Indonesia. This research employed selected top manufacture companies listed in West Java-Indonesia. There were 110 respondents distributed as primary data that were obtained by distributing a structured questionaires to marketing managers or director (or the manager involved in marketing activities). Data analysis was conducted through the 100 returned questionaires (91 % respond rate valid for data analysis). The results of the study showed that marketing mix variables was applied in business practices. The reactions of the respondent toward mix variables and organizational variable mean was high in 4.12 and 4.04. The size of the variables are represented in the form of numbers starting from 1, 2, 3, 4 and 5. Thus the numbers 4.12 and 4.04 mean that 4P's variables and organizational goal variables are variables that play an important role in business organizations. Correlation of each product, price, promotion and place shows a positive direction and a strong relationship to organizational goals. And simultaneously the direction remains positive with a very strong relationship. Furthermore, the achievement of organizational goals can be predicted by using multiple linear regression where organizational goals are influenced by product strategy, price, promotion and place where Organizational goal = 0.25 + 0.20 product + 0.30 price + 0.41 promotion + 0, 18 place. And each independent variable (t-test) significantly influences the achievement of organizational goals. Likewise, simultaneously (F-test) independent variables significantly influence the achievement of organizational goals.